Электрическая машина с двухсторонним статором, осевым магнитным потоком, постоянными магнитами и многослойными печатными обмотками - Гребеников, Виктор Владимирович; Гамалея, Ростислав Витальевич; Попков, Владимир Сергеевич; Соколовский, Александр Николаевич; Богаенко, Николай Владимирович (Национальный технический университет "Харьковский политехнический институт", 2020)
Применение печатных обмоток в электрических машинах с постоянными магнитами и осевым магнитным потоком позволяет уменьшить их осевой размер и существенно увеличить плотность тока в обмотках из-за малой толщины и соответственно большой ширины проводников печатной обмотки и как следствие лучшего их охлаждения. Изготовлен опытный образец электрической машины с двухсторонним статором, многослойными печатными обмотками и постоянными магнитами цилиндрической формы. Определены зависимости напряжения и мощности в генераторном режиме при подключении обмоток через диодный мост к нагрузке. Расчетная модель генератора адекватно описывает физическую модель. Расхождение между расчетными и экспериментальными значениями не превышает ε = 4%. Расчет характеристик исследуемых генераторов выполнялся в пакетах программ Simcenter MagNet и Simcenter MotorSolve.

The use of printed windings in electric machines with permanent magnets and axial magnetic flux allows to reduce their axial size and significantly increase the current density in the windings due to the small thickness and correspondingly large width of the conductors of the printed winding and, as a result, their better cooling. The dependences of voltage and power in the generator mode are determined when connecting the windings through the diode bridge to the load. Investigations of the effect of stator teeth on the magnitude of the electromagnetic torque are made. It was found that the presence of teeth on the stator allows you to increase the electromagnetic torque of the electric machine by about 26% compared with the ve rsion of the magnetic system without teeth. The effect of the displacement of one stator relative to another on the magnitude of the tooth torque has been studied. A prototype of an electric machine with a double-sided stator, multilayer printed windings and permanent cylindrical magnets was manufactured. The calculated model of the generator adequately describes the physical model. The discrepancy between the calculated and experimental values does not exceed ε = 4%. The characteristics of the studied generators were calculated by the software packages Simcenter MagNet and Simcenter MotorSolve.
The electric machine with two-sided stator, axial magnetic flux, permanent magnets and multilayered printing windings
Keywords: электромагнитный момент; внешние характеристики; экспериментальный образец; electromagnetic torque; external characteristics; experimental sample